Functional comparison of pacifiers using finite element analysis - David A. Tesini; Linda C. Hu; Brent H. Usui; Christopher L. Lee (BMC, 2022)
Abstract Background Pacifiers have been shown to affect maxillary growth related to the anatomic structure of the palate and forces placed upon it during sucking. This study compares and evaluates the mechanical behavior of pacifiers of different design and size (i.e., fit), identified by brand and size, positioned in age-specific palatal models with respect to both contact area and force when subjected to peristaltic tongue function and intraoral pressure related to non-nutritive sucking. Methods Nonlinear finite element analyses were used to simulate dynamic mechanical interaction between the pacifiers and palates. Time-varying, external pressure loads were applied which represent intraoral pressure arising from non-nutritive sucking and peristaltic behavior of the tongue. The silicone rubber pacifier bulb was represented using a hyperelastic material model. Results Results from the finite element analyses include deformation, stress, strain, contact area, and contact force. Mechanical interaction was evaluated in terms of the spatial distribution of the contact area and force between the pacifier and the palate. The resulting palatal interaction profiles were quantitatively compared to assess how pacifier fit specifically affects the support provided to two areas of the palate, the palatal vault and the Tektal wall. Conclusions Pacifiers interact with the palate differently based on their fit (i.e., design and size) regardless of whether they are labeled conventional or orthodontic. Finite element analysis is an effective tool for evaluating how a pacifier's design affects functional mechanics and for providing guidance on biometric sizing.